Sinomenine Alleviates Rheumatoid Arthritis by Suppressing the PI3K-Akt Signaling Pathway, as Demonstrated Through Network Pharmacology, Molecular Docking, and Experimental Validation - Liu Q; Wang J; Ding C; Chu Y; Jiang F; Hu Y; Li H; Wang Q (Dove Medical Press, 2024)
Qingyang Liu,1,* Jian Wang,2,* Chunhui Ding,3 Ying Chu,1 Fengying Jiang,1 Yunxia Hu,4 Haifeng Li,2 Qiubo Wang1 1Department of Clinical Laboratory, Wuxi Ninth People's Hospital Affiliated to Soochow University, Wuxi, Jiangsu, 214000, People's Republic of China; 2Department of Orthopedics, Wuxi Ninth People's Hospital Affiliated to Soochow University, Wuxi, Jiangsu, 214000, People's Republic of China; 3Department of Pharmacy, Wuxi Ninth People's Hospital Affiliated to Soochow University, Wuxi, Jiangsu, 214000, People's Republic of China; 4Department of Rheumatology and Immunology, The Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi, Jiangsu, 214000, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiubo Wang, Department of Clinical Laboratory, Wuxi Ninth People's Hospital Affiliated to Soochow University, No. 999 Liang Xi Road, Binhu District, Wuxi, Jiangsu, 214000, People's Republic of China, Email wangqiubo2020@suda.edu.cn Haifeng Li, Department of orthopedics, Wuxi Ninth People's Hospital Affiliated to Soochow University, No. 999 Liang Xi Road, Binhu District, Wuxi, Jiangsu, 214000, People's Republic of China, Email lihaifeng2008@suda.edu.cnPurpose: Sinomenine (SIN) is commonly used in Traditional Chinese Medicine (TCM) as a respected remedy for rheumatoid arthritis (RA). Nevertheless, the therapeutic mechanism of SIN in RA remains incompletely understood. This study aimed to delve into the molecular mechanism of SIN in the treatment of RA.Methods: The potential targets of SIN were predicted using the TCMSP server, STITCH database, and SwissTarget Prediction. Differentially expressed genes (DEGs) in RA were obtained from the GEO database. Enrichment analyses and molecular docking were conducted to explore the potential mechanism of SIN in the treatment of RA. In vitro and in vivo studies were conducted to validate the intervention effects of SIN on rheumatoid arthritis, as determined through network pharmacology analyses.Results: A total of 39 potential targets associated with the therapeutic effects of SIN in RA were identified. Enrichment analysis revealed that these potential targets are primarily enriched in PI3K-Akt signaling pathway, and the molecular docking suggests that SIN may act on specific proteins in the pathway. Experimental results have shown that exposure to SIN inhibits cytokine secretion, promotes apoptosis, reduces metastasis and invasion, and blocks the activation of the PI3K-Akt signaling pathway in RA fibroblast-like synoviocytes (RA-FLS). Moreover, SIN treatment alleviated arthritis-related symptoms and regulated the differentiation of CD4+ T cells in the spleen of collagen-induced arthritis (CIA) mice.Conclusion: By utilizing network pharmacology, molecular modeling, and in vitro/in vivo validation, this study demonstrates that SIN can alleviate RA by inhibiting the PI3K-Akt signaling pathway. These findings enhance the understanding of the therapeutic mechanisms of SIN in RA, offering a stronger theoretical foundation for its future clinical application. Keywords: sinomenine, rheumatoid arthritis, network pharmacology, PI3K-Akt signaling pathway